Clinical significance of unexplained persistent sinus tachycardia in women with structurally normal heart during the peripartum period - Dimitrios Varrias; Nikhil Sharma; Roland Hentz; Rosaline Ma; Dillon Gurciullo; Jeremy Kleiman; Andrew Kossack; Eliot Wolf; Betty Lam; Tia Bimal; Umair Ansari; Kristie M. Coleman; et al. (BMC, 2022)
Abstract Background Persistent sinus tachycardia (ST) is frequently encountered during pregnancy and peripartum period and its etiology often remains elusive. We sought to examine the possible association between unexplained persistent ST and obstetric outcomes. Methods A case control study was conducted using chart review of women admitted in labor to one of 7 hospitals of Northwell Health between January 2015 to June 2021. After excluding women with structurally abnormal hearts, we identified patients with persistent ST during the peripartum period, defined as a heart rate of more than 100 bpm for more than 48 h. A control group was created by randomly subsampling those who did not meet the inclusion criteria for sinus tachycardia. Obstetric outcomes were measured as mother's length of stay (LOS), pre-term labor (PTL), admission to the neonatal ICU (NICU), and whether she received cesarean-section (CS). Results Seventy-eight patients with persistent ST were identified, out of 141,769 women admitted for labor throughout the Northwell Health system. 23 patients with ST attributable to infection or hypovolemia from anemia requiring transfusion and 55 with unclear etiology were identified. After adjusting for age and parity, pregnant mothers with ST were 2.35 times more likely to have a CS than those without (95% CI: 1.46-3.81, p = 0.0005) and had 1.38 times the LOS (1.21- 1.56, p < 0.0001). Among mothers with ST, those with unexplained ST were 2.14 times more likely to have a CS (1.22-3.75, p = 0.008). Conclusion Among pregnant patients, patients with ST have higher rates of CS.This association is unclear, however potential mechanisms include catecholamine surge, indolent infection, hormonal fluctuations, and medications. More studies are needed to explore the mechanism of ST in pregnant woman to determine the clinical significance and appropriate management.